Methylsulfonyl PCB and DDE metabolites and their enantioselective gas chromatographic separation in human adipose tissues, seal blubber and pelican muscle - Karásek, L; Hajšlová, Jana; Rosmus, Jan; Huhnerfuss, Heinrich (Chemosphere, 2007)
In the present investigation, eleven human adipose tissue samples, two seal blubber samples and two pelican muscles samples were analyzed with regard to their concentrations of PCB parent compounds as well as to the respective chiral methylsulfonyl metabolites 3-MeSO2-CB 91, 4-MeSO2-CB 91, 3-MeSO2-CB 95, 4-MeSO2-CB 95, 3-MeSO2-CB 149, 4-MeSO2-CB 149, 3-MeSO2-CB 132, 4-MeSO2-CB 132, 3-MeSO2-CB 174, and 4-MeSO2-CB 174 and the achiral metabolites 3-MeSO2-CB 49, 4-MeSO2-CB 49, 3-MeSO2-CB 101, 4-MeSO2-CB 101, 3-MeSO2-CB 110, 4-MeSO2-CB 110 and 3-MeSO2-DDE. In order to verify enantioselective transformation processes and to compare the different enzymatic transformation pathways in birds and mammals, the enantioselective excesses of the chiral PCB-metabolites were determined by enantioselective gas chromatography with electron capture and mass spectrometric detection using modified cyclodextrin phases, including heptakis(2,3-di-O-methyl-6-O-tert-butyldimethylsilyl-)-beta-cyclodextrin/OV1701 (1:1) for the parent PCBs and heptakis(2,3-di-O-methyl-6-O-tert-butyldimethylsilyl-)-beta-cyclodextrin/SE52 (1:4) for the metabolites, respectively.
Keywords: Animals; svaly; dichlordifenyldichlorethylen; Polychlorinated Biphenyls; tuleňovití; polychlorované bifenyly; cyklodextriny; lidé; Cyclodextrins; Dichlorodiphenyl Dichloroethylene; Stereoisomerism; stereoizomerie; Seals, Earless; plynová chromatografie s hmotnostně spektrometrickou detekcí; methansulfonáty; Environmental Pollutants; Gas Chromatography-Mass Spectrometry; Muscles; zvířata; tuková tkáň; látky znečišťující životní prostředí; Adipose Tissue; Mesylates; Humans